# In each of the following, use factor theorem to find whether polynomial g(x) is a factor of polynomial f(x) or, not:f(x) = 2x3-9x2+x+12, g(x) = 3-2x

We have,

f(x) = 2x3-9x2+x+12 and g(x) = 3-2x

In order to find g (x) = 3 – 2x = 2 (x - ) is a factor of f (x) or not, it is sufficient to prove that f ( ) = 0

Now,

f(x) = 2x3-9x2+x+12

f ( ) = 2 ( )3 – 9 ( )2 + + 12

= - + + 12

= = 0

Hence, g (x) is a factor of f (x).

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Basic understanding of Polynomials37 mins  Quiz | Division of Polynomials38 mins  Polynomials - Zero to Hero42 mins  Genius Quiz | Polynomials40 mins  Zeros and Degrees of a Polynomial41 mins  Genius Quiz | Division of Algebraic Expressions37 mins  Champ Quiz | Polynomials29 mins  Introduction to Polynomials37 mins  Quiz | Imp. Qs. on Algebraic Identities65 mins  NCERT | Various Methods of Factorization39 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

Factorize:

x3 – 2x2y + 3xy2 – 6y3

RS Aggarwal & V Aggarwal - Mathematics

Factorize:

a2 + a – 3a2 - 3

RS Aggarwal & V Aggarwal - Mathematics

Factorize:

2a(x + y) -3b(x + y)

RS Aggarwal & V Aggarwal - Mathematics

Factorize:

8 – 4a – 2a3 + a4

RS Aggarwal & V Aggarwal - Mathematics

Factorize:

a2 + ab(b + 1) + b3

RS Aggarwal & V Aggarwal - Mathematics